A quantitative research on the level of disturbance to secondary signal ports of electronic voltage transformers under the operation of gas‐insulated switchgear. (14th June 2021) - Wang, Qi; Fu, Chao; Chu, Fanwu; Tong, Yue; Wang, Xiaozhou; Ye, Guoxiong; Wu, Xiong
Abstract: The collectors of electronic transformers has the problem of electromagnetic incompatibility under the operation of disconnecting switches, which limits their wide application in smart grids. To evaluate the maximum level of disturbance that collectors are able to withstand in the stochastic process of switching operation, this work introduces a quantitative approach based on limited test measurements, which can quantify the level of disturbance in the signal acquisition ports of electronic voltage transformers (EVT) in different gas‐insulated switchgears (GIS). Based on large numbers of experimental statistical data of the true type simulation experimental platform, the Spearman rank correlation coefficient is used to prove that the amplitude of the disturbance voltage pulse at the secondary side port and the breakdown voltage between the primary side fracture approximately satisfy a linear relationship. Subsequently, the quantile regression model is used to quantify and verify the maximum disturbance level of the secondary side port. Moreover, a solution is proposed to tackle the difficulty in obtaining the breakdown voltage at breaks in the GIS substation field applicatvion, under which the quantified maximum disturbance voltage deviation of secondary ports is only −4.34% by comparison. The research work can further explore the practical value of the measured data in a few tests under GIS substation field conditions and provide references for the subsequent revision of EVT‐related standards.